‘Dens of loitering lubbers’: protestant protest against cathedral foundations, 1540–1640 - Cross, Claire (Studies in church history, 1972)
In A View of Popishe Abuses which enlarged upon the corruptions remaining in the English church, already itemised by protestant radicals in An Admonition to the Parliament of 1572, the writer dwelt at some length upon the iniquities of cathedral foundations.We should be too long to tell your honours of cathedral churches, the dens aforesaid of all loitering lubbers, where master dean, master vicedean, master canons or prebendaries the greater, master petty canons or canons the lesser, master chancellor of the church, master treasurer, otherwise called Judas the pursebearer, the chief chanter, singingmen, special favourers of religion, squeaking choristers, organ players, gospellers, pistellers, pensioners, readers, vergers etc. live in great idleness and have their abiding. If you would know whence all these came, we can easily answer you, that they came from the pope, as out of the Trojan horse’s belly, to the destruction of God’s kingdom. The church of God never knew them, neither doth any reformed church in the world know them.